(untitled) (International journal of artificial intelligence, 2026)
In this article, Shukur Kholmirzayev's belief in the traditions of folk art, cultural and spiritual wealth of his people, his belief and interest in the traditions existing in folk art is a specific social ground. The writer himself is without nature, without his own destiny, his spiritual wealth is expressed in the thoughts of the author.